Vi. Uṇṇikrṣṇan Nāyar : śatābhiṣēkōpahāraṃ - Unnikrishnan Nair, K., 1893-; Kēśavamēnōn, Ke. Pi., 1886-1978 (Vi. Uṇṇikrṣṇan Nāyar Śatābhiṣēkāghōṣakammiṯṯi, 1977)
Festschrift honoring V. Unnikrishnan Nair, b. 1893, Malayalam writer; articles on his life and writings.